Application of Greenhouse Technology for Solar Drying of Industrial Sludge- Preliminary Results - Rotich , Justus Kimurgor; Tonui , Joel K.; Ndalut , Paul K.; Bore , Ezekiel K.; Njoroge , Joseph N.; Macharia , Peter (African Journal of Education,Science and Technology (AJEST), 2013)
The application of solar drying of industrial sludge was conducted inside a greenhouse dryer at the University of Eldoret (UOE). Many industrial processes, such as food processing plants, discharge huge amount of wastewater that is usually treated before disposing. The Agrochemical and Food Company (ACFC Ltd), Muhoroni, discharges about 1.2 million litres daily from the production of industrial spirits through the fermentation of molasses. In this paper, preliminary results are presented on pilot drying experiments performed on liquid sludge discharged from the ACFC Ltd molasses processing plant. The liquid sludge was put on three rectangular containers to different depths and placed inside a greenhouse to dry until a constant mass of dry bio-solids were obtained. The masses and temperatures of the sludge in each container as well as the operating conditions (solar radiation and ambient temperature) were measured at equal time intervals of one hour during the day and recorded for use in the analysis. The results showed the moisture content of the samples to be 90.44%, 90.65% and 90.35% and the overall drying effectiveness of 0.54, 0.44 and 0.26 for the heights 2, 4 and 8 cm respectively. From these results, the most effective height for sludge drying under the prevailing climatic conditions of Eldoret is 2cm with an efficiency of 54%. However, the surface area needs to be increased in order to increase the yield per drying batch